Redefining Parental Involvement in Competency Based Curriculum Implementation in Kenya. A Critical Review - Cherui, Rodgers Gowon; Kipkenei S. (African Journal of Business, Economics and Industry, 2025)
Kenya has made significant strides in implementation of the Competency-Based Curriculum. However, there have beenchallenges, which the s government has been trying to address. Parents have raised concerns about their involvement in their children’s academic work and their increased role in the implementation of the new curriculum. The purpose of this study wasto review literature on and redefine parental involvement inimplementation of Competency Based Curriculum.The study was guided by the Structural Functionalism Theory by Emile Durkheim guided the paper. Desktop critical review of various journal articles and other secondary sources was carried out. The studyestablished a great concern of parentsthat the new curriculum is resource expensive and demands ofthemto be involved in the implementation of thecurriculum. Parental involvement includes helping learners in the entire learning process and in doing assignments. The new curriculum does not only focus on academic work but also non-academic work and therefore, forcing parentsto assume roles in holistic development of their children. Since the focus of the curriculum is on the competencies, feedback from parents is very vital in complementing teachers’ role especially in guiding their children to choosethe right pathway in senior school. There is a need for constant communication between the teachers in the process. The expanded role of parents in implementation of the new curriculum should be explained well so as to overcome the teething problems that are being associated with the Competency Based Curriculum
journal article
Keywords: parental involvement; competency-basedcurriculum; nonacademic; pathway